Prevalence of joint hypermobility, hypermobility spectrum disorder and hypermobile Ehlers-Danlos syndrome in a university population: an observational study - Tuna, Filiz (The European Research Journal, 2020)
Objectives: To investigate the prevalence of joint hypermobility classes, hypermobility spectrum disorders, hypermobile Ehlers-Danlos syndrome and their relations with sex ina university population. They are notable topics in rehabilitation, since they represents the basis for some secondary disability conditions.Methods: Three hundred and thirty-five students met the inclusion criteria (university students who are not disabled, without known disease, aged 18-25 years). Joint hypermobility were classified as generalized, peripheral and localized asymptomatic or hypermobility spectrum disorders. Hypermobile Ehlers-Danlos syndrome was defined according to; 1) Brighton criteria with cut-off Beighton scoring ≥ 4/9, 2) Villefranche criteria with cut-off Beighton scoring ≥ 5/9, and 3) The 2017 International Classification of Ehlers-Danlos syndrome.Results: In total, 77.3% (n = 259) of participants had any class of joint hypermobility and 25.9% (n=87) of them had generalized class. Asymptomatic joint hypermobility and hypermobility spectrum disorders prevalence in a university population were found to be 38.8% and 38.5%, respectively. Generalized, peripheral, localized asymptomatic joint hypermobility and hypermobility spectrum disorders were found; 13.1%, 4.2%, 21.5%, and 12.8%, 7.5%, 18.2%, respectively. Prevalence of hypermobile Ehlers-Danlos syndrome according to three classifications were found to be; 19.4%, 15.2%, and 1.2%, respectively. Conclusions: The most common classes are localized asymptomatic joint hypermobility in women and localized hypermobility spectrum disorders in men. Awareness of the prevalence of joint hypermobility, hypermobility spectrum disorders and hypermobile Ehlers-Danlos syndrome in healthy young population may contribute prevention of disability.